Company Satisfaction, Company Commitment and Work Involvement : An Empirical Examination of Blue Collar - Baba, Vishwanath; Jamal, Muhammad (Relations industrielles / Industrial Relations, 1976)
This study investigates the relationships among Company satisfaction, company commitment and work involvement for a sample of blue-collar workers drawn from packaging, power distribution and manufacturing industries in Canada. Guttman scaling, factor analysis and correlational analysis are the statistical techniques employed to analyze the data. The results confirms the hypothesized positive relationship among the three attitudes.